Pengembangan Sistem Informasi Geografis Menggunakan YWDM Dalam Perencanaan Tata Ruang - Fauzi, Cholid (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Spatial Planning Geographical Information System is an information system built to support spatial requirements in building urban planning; where this application is built to visualize how a spatial plan consisting of spatial patterns and spatial structures is planned. In developing web-based GIS applications, software development methodologies are usually used to develop in this study. Y-Model Webgis Development (YWDM) which is a combination of geographic information system engineering and web-based application development context. This methodology applies map-based visualization to urban planning and development. Applications that are expected to be able and appropriate to meet the needs accurately following the existing conditions of space utilization. Data processing uses Geoserver for servers, Postgresql for creating spatial data, and JavaScript programming language to visualize the results of planning and utilization of urban spatial planning. The results show that application development becomes easier and software requirements can be well defined because the requirements of the software development context and spatial specifications are met, even though in this research only to stage GIS Integration. After all, after this stage, it is carried out like the usual software development stage. With the implementation of this methodology, it is evident that GIS web application development can be easier, and with the needs desired by users.